Genetic relationships among Eurasian Puccinellia distans genotypes. (October 2015) - Bar, Cantuğ; Doğanlar, Sami; Frary, Anne
Abstract: Puccinellia distans (Jacq.) Parl . is a common grass species found throughout the world. It can grow in arid and saline environments as well as under toxic boron concentrations. In this work we performed sequence related amplified polymorphism (SRAP) marker analysis on 20 wild P . distans genotypes to understand the genetic relationships among different genotypes and subspecies. We tested 119 SRAP primer pairs and found that 43 were polymorphic. The molecular data were then analyzed to determine the genetic relationships and population structure of the genotypes. We were able to trace the origin of genotypes that were carried to distant locations or gathered for research purposes. We also found that geographical distance between genotypes was not an important determinant of genetic relationships as even distantly located Puccinellia genotypes were closely related. As P . distans is known to be tolerant to salinity stress and toxic mineral concentrations, the findings of this work can be used as a starting point for selection of genotypes that should be tested under such conditions. Highlights: We investigate the relationship between Puccinellia distans genotypes. Only P . distans subspecies borealis was distinct from the other P . distans genotypes and subspecies. There was only moderate correlation between genetic distance and collection location.